2015
DOI: 10.1155/2015/684925
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds fromOlea europaeaL. Possess Antioxidant Activity and Inhibit Carbohydrate Metabolizing EnzymesIn Vitro

Abstract: Phenolic composition and biological activities of fruit extracts from Italian and Algerian Olea europaea L. cultivars were studied. Total phenolic and tannin contents were quantified in the extracts. Moreover 14 different phenolic compounds were identified, and their profiles showed remarkable quantitative differences among analysed extracts. Moreover antioxidant and enzymatic inhibition activities were studied. Three complementary assays were used to measure their antioxidant activities and consequently Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
5
40
0
Order By: Relevance
“…The VOO stability against oxidation is due to its content of phenolic compounds (Dekdouk et al, ). In the present study, a direct quantification of each secoiridoid aglycone based on calibration curves was not possible, because no standard was available for the detected species.…”
Section: Resultsmentioning
confidence: 99%
“…The VOO stability against oxidation is due to its content of phenolic compounds (Dekdouk et al, ). In the present study, a direct quantification of each secoiridoid aglycone based on calibration curves was not possible, because no standard was available for the detected species.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of lipid peroxidation of wood extracts was assayed by the BCB method . Butylated hydroxytoluene (BHT) was used as a positive control for the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…65 Recently, phenolic composition with tannin contents and their biological activities of fruit extracts from Italian and Algerian Olea europaea L. cultivars were studied. 40 Fourteen different phenolic compounds including hydroxytyrosol, tyrosol, p-hydroxybenzoic acid, and verbascoside as major constituents were identified, and their profiles showed remarkable quantitative differences among analyzed extracts. The authors reported that there were no significant qualitative differences among samples, but it is possible to note important quantitative differences.…”
Section: Chemical Composition Of Crude Extracts Of O Europeamentioning
confidence: 98%
“…28,[30][31][32][33][34][35][36][37][38] Recently, an increase interest in natural substances extracted from such plants has been observed in literatures due to their significant impact from an environmental point of view, as well as to find effective alternatives to the industrially synthesized chemicals. 3,[39][40][41][42] Therefore, the objective of this study was to analyze the chemical composition of acetone extracts of Pinus halepensis Mill (needles and bark) and Olea europaea L. (leaves and barks), collected from three levels of altitude in AL-Jabal AL-Akhder, Libya, using gas chromatography/mass spectrometry (GC/MS). The GC/MS is an analytical instrument that a hyphenated system of GC and MS and it is a very compatible technique and the most commonly used technique for the identification and quantification of different substances within a test sample.…”
Section: Introductionmentioning
confidence: 99%